DYNAMICS OF THREE-LAYER INHOMOGENEOUS CYLINDRICAL SHELLS ON AN ELASTIC BASE UNDER NON-STATIONARY LOAD - Orlenko, S.P. (Reports of the National Academy of Sciences of Ukraine, 2024)
Layered cylindrical shells are widely used as structural components of machines, space and aircraft, various buildings, and other units. To date, the problems of dynamic interaction of inhomogeneous shell structures with elastic media have been insufficiently investigated. The use of lightweight aggregate results in a special three-layer structure that has a fairly high flexural rigidity with a favorable strength-to-weight ratio. With significant differences in the physical and mechanical parameters of the layers, it is advisable to apply shell theories using independent hypotheses for each of the layers. In this work, the dynamics of a three-layer cylindrical shell on an elastic Winkler base under various boundary conditions under unsteady loads is considered. The material properties of adjacent layers differ significantly, so it is reasonable to use the finite element method for calculations of such shell structures. The study of dynamic processes in such complex three-layer structures with significant changes in their geometric and physical parameters is of great interest for design developments.